Design of Decision Support System for Food Selection for Diabetes Mellitus Type 2 Using Weighted Product Method (Case Study: Puskesmas Temon II Kulon Progo) - Amalia Nur Afifah; Arizona Firdonsyah (Procedia of Engineering and Life Science, 2021)
DM is known as cardiovascular disease, but DM is also one of the main causes of kidney disease and blindness under 65 years of age, as well as amputation. DM is also a cause of amputation (which is not caused by trauma), disability, and death. Another effect of diabetes is to reduce life expectancy by 5-10 years. The life expectancy of people with type 2 diabetes mellitus or non-insulin-dependent diabetes mellitus who suffer from serious mental illnesses, such as schizophrenia, is even 20% lower than the general population. The method to be used is the Weighted Product (WP) method. This method is used because the WP is one of the preferred methods for solving complex problems and can produce structured calculations. The ranking result states that the alternative Tempe Boiled with a value of 0.136 is the best suggestion for the user.